School impact factors on North Korean migrant youths’ self-esteem : love & servant leadership as the essence - Kang, Gee Hae (2020)
Since after mid-90s when North Korean have had severe state crisis, there has been an up surging migrants to South Korea, and their children have been estimated to be considerable numbers in South Korea. However, the children have had obvious challenges in their everyday life including families, homes, and schools due to their migrations, thus, their adaptation and integration into South Korea requires physical and psychological support. In the meantime, self-esteem has been known to have mediating role for stress, resilience, and intercultural adaptation. In this sense, the study tackles on psychological support in terms of enhancing their self-esteem in school settings. In order to research, this study selected a case school specialized in the education for North Korean migrant youths in South Korea. Therefrom, 9 senior students, 3 graduates, and 3 educators were participated for data collection. The study adopted two measures for the research, employing Rosenberg Self-Esteem Scale (1965b) survey for measuring self-esteem and conducting semi-structured qualitative interviews. For analysis, the data were analysed by thematic analysis inductively. The findings revealed that there had been four elements as relationships, faith, education, extra activity programs, and as one of the most critical factor, school value and educational leadership exerted by the school teachers were the supportive school components that fostered students’ self-esteem. As a result, love and servant leadership were concluded as the most significant factors. At last, this study provides a new interpretation of the students’ self-esteem with the value of love and the aspect of growing them through servant leadership.